C=N-containing azaarenes as activating groups in enantioselective catalysis - Best, Daniel; Lam, Hon Wai (American Chemical Society, 2013)
Nitrogen-containing aromatic heterocycles (azaarenes) are of widespread chemical significance, and chi-ral compounds containing azaarenes feature prominently in pharmaceuticals, agrochemicals, and natural products. This Perspective highlights the use of a relatively underdeveloped strategy to prepare chiral azaarene-containing compounds: exploitation of the C=N bond embedded within certain azaarenes to activate adjacent functionality in catalytic asym-metric reactions. Work in this area has resulted in the development of several different types of catalytic enantioselec-tive processes, including reductions, nucleophilic additions, and reductive couplings. It is hoped that this Perspective will encourage more researchers to work in this promising area.